A Pilot Study for Improving Classroom Systems Within Schoolwide Positive Behavior Support. (March 2019) - Oliver, Regina M.; Lambert, Matthew C.; Mason, W. Alex
Despite the overall success of Schoolwide Positive Behavior Support, there is evidence teachers do not effectively utilize Schoolwide Positive Behavior Support features in the classroom. Classrooms are important systems within a Schoolwide Positive Behavior Support framework as this is the location within the school that students spend the majority of their time. This is especially important for students with emotional and behavioral disorders as teacher proficiency with classroom management affects the progression and malleability of the disorder. The purpose of this study was to examine the use of a manualized classroom management program to improve classroom atmosphere and teacher use of classroom management practices within schools already utilizing Schoolwide Positive Behavior Support with fidelity. Results suggest significant improvements in teacher use of certain classroom practices (e.g., praise) and classroom systems. Strengths and limitations of the study are presented along with implications for research and practice.